Die deutsche Ausgabe von Le Monde diplomatique zwischen national und international – Rekonfiguration einer journalistischen Alternative - Lisa Bolz (Recherches Germaniques)
The German version of Le Monde diplomatique has an exceptional position among German newspapers and stands out because of a double challenge: On the one hand it is a cross between the French version (whose name it bears) and the German daily taz (whose supplement it is). On the other hand it presents a variety of international subjects to a German readership. The French version and taz constitute alternative journalistic environments, but the German version of Le Monde diplomatique does not have an alternative editorial structure. It displays mainly an alternative with regards to the content, adopted from the French version and adapted to the own readership. In this case alternative journalism is not only defined with reference to the structure or the organisation, but based on the construction of an alternative thematic agenda. By means of a certain selection and presentation of news a counter public space is created which is not a journalistic discourse beyond the mass media, but rather an alternative media proposition.